A NEW GENERATION OF SWITCHES - Kornoukhova, K. V.; Myroshkin, V. O. (Science and Transport Progress, 2006)
Technical descriptions of new pointer translations, and also short information, about application in pointer translations of supporting rollers for facilitation of moving of wits are resulted in the article